Correlation of anemia in pregnancy and low birth weight in public health centers - Rony Sibuea; Sarma Nursani Lumban Raja (Institute of Computer Science (IOCS), 2022)
This study aims to look at the prevalence of anemia and LBW and also evaluate the correlation of anemia in pregnancy with LBW. This study method is observational analytic approach named cohort retrospective. It is used to analyze the correlation between the incidence of LBW and anemia in pregnancy located in the Public Health Center of Pulau Untung Jawa Village, Kepulauan Seribu Selatan Sub-District, DKI Jakarta. The acquisition data was obtained for the period January – July 2022 where the samples of all babies born and all mothers who gave birth at the Public Health Center. The number of samples obtained 39 samples. This study used inclusion criteria, namely infants with LBW and not LBW and also their mothers, pregnant women who were anemic and not anemic. Beside, they had exclusion criteria that include mothers with a history of premature birth. Researchers took samples by collecting data in the medical record of childbirth in 2022 by taking data in the form of samples of baby weight after birth, maternal delivery data, maternal and infant identity, gestational age, Hb status, parity, and antenatal care data. Data obtained on the anemia prevalence in respondents at the Public Health Center is mild anemia of 15%, then 75% moderate anemia, severe anemia of 7,5%, and no anemia as much 2,5%. So, it can be concluded that the highest prevalence of anemia is moderate anemia. Results of p value > 0.05 and OR = 0,147 which means that there is no significant correlation between anemia in pregnancy on LBW and mothers with anemia. It will occur smaller LBW rather than in mothers with a history of anemia.